Formulasi Fraseologi Frase Tetap dalam Komunikasi ATC: Perspektif Linguistik Terapan - Ismaliyah Yusuf Rangkuti; Evi Novianti; Nindi Aristi (Balai Bahasa Provinsi Bali, 2025)
Communication between pilots and air traffic controllers (ATC) in the aviation sector is supported by a standardized language system known as phraseology, particularly through the use of fixed phrases established by the ICAO. This study focuses on analyzing the formulation of fixed phrase phraseology in ATC communication from an applied linguistics perspective. The research aims to contribute significantly to the understanding of technical language within the aviation context and to enhance professional communication practices in support of optimal flight safety. Using a qualitative approach through a case study conducted at AirNav Indonesia (JATSC), data were collected via interviews, direct observations, and literature reviews. The main findings reveal that fixed phrases play a crucial role in delivering instructions quickly, clearly, and unambiguously, especially in critical or emergency situations. The applied linguistic analysis indicates that sentence structures in phraseology are formulaic and imperative in nature, designed to minimize the risk of communication errors. Furthermore, continuous training for ATC personnel is identified as a key factor in ensuring the accurate and context-appropriate use of phraseology. Adjustments to fixed phrases may occur in exceptional situations, yet these modifications are made without compromising clarity of meaning. This study underscores the importance of phraseology as a form of technical communication that prioritizes safety within the global aviation system. AbstrakKomunikasi antara pilot dan pengendali lalu lintas udara (ATC) dalam dunia penerbangan ditopang oleh sistem bahasa terstandar yang disebut fraseologi, khususnya melalui penggunaan frase tetap yang ditetapkan oleh ICAO. Penelitian ini bertujuan berfokus pada analisis formulasi fraseologi frase tetap dalam komunikasi ATC dari perspektif linguistik terapan. Penelitian ini diharapkan dapat memberikan kontribusi penting terhadap pemahaman bahasa teknis dalam konteks penerbangan dan meningkatkan praktik komunikasi profesional demi keselamatan penerbangan yang optimal. Dengan menggunakan pendekatan kualitatif melalui studi kasus di AirNav Indonesia (JATSC), data dikumpulkan melalui wawancara, observasi langsung, serta kajian literatur. Temuan utama menunjukkan bahwa frase tetap memainkan peran penting dalam menyampaikan instruksi secara cepat, jelas, dan tanpa ambiguitas, terutama dalam kondisi kritis atau darurat. Analisis linguistik terapan memperlihatkan bahwa struktur kalimat dalam fraseologi bersifat formulaik dan imperatif, yang ditujukan untuk mengurangi risiko kesalahan komunikasi. Selain itu, pelatihan berkelanjutan bagi petugas ATC menjadi faktor penting untuk memastikan penggunaan fraseologi yang akurat dan kontekstual. Penyesuaian frase tetap dalam situasi luar biasa pun dilakukan tanpa mengorbankan kejelasan makna. Studi ini memperkuat pentingnya fraseologi sebagai bentuk komunikasi teknis yang mengedepankan keselamatan dalam sistem penerbangan global.